pemberdayaan lembaga amil zakat masjid rungkut jaya surabaya dalam meningkatkan kesejahteraan mustahiq - Rizky Farah Nurfadhilah; Ririn Tri Ratnasari (Universitas Airlangga, 2019)
The research used in this paper is a qualitative research method with descriptive analytical case study method, which is an analysis that produces descriptive data in the form of written or oral words from people and behaviors that can be observed with a predetermined method. The purpose of this method is to minimize the results of research difficult to manipulate because researchers have little chance to control events that will occur. The event in question is the empowerment of the Rungkut Jaya Surabaya Mosque Amil Zakat Institution in improving mustahiq welfare, so that the data needed is not enough historical data but interviews are needed, and direct observation in the field. The research data was collected by interviewing the Chairperson of the LAZ Masjid Rungkut Jaya, the Chair of Ta'mir, 2 mustahiq LAZ Masjid Rungkut Jaya, and 2 muzakki LAZ Masjid Rungkut Jaya.Keywords: Empowerment of Amil Zakat Institutions, Amil Zakat Institutions, Zakat, Empowerment of Amil Zakat Institutions in Rungkut Jaya Mosque Surabaya, MustahiqREFERENCES Al-Ba’ly, Abdul Al Hamid Mahmud. 2006. Ekonomi Zakat: Sebuah Kajian Moneter dan Keuangan Syariah. Jakarta: PT. Raja Grafindo Persada. hlm. 1.Al-Ghazali, Ihya Ulumuddin, Juz II, Mesir: Multazam At-Taba’ Wannasar, t,t.Ali, M. Daud. 1998. Sistem Ekonomi Islam Zakat dan Waqaf. Jakarta: UI-Press. hlm. 39.Arifin, Zainul. Memahami Bank Syari’ah Lingkup, Peluang, Tantangan dan Prospek. Jakarta: Alvabet, 2000.Ash-Shiddieqy, Muhammad Hasbi. 2009. Pedoman Zakat. Semarang: PT. Pustaka Rizki Putra. hlm. 162.Asnaini. 2007. Zakat Produktif Dalam Perspektif Hukum Islam. Yogyakarta: Pustaka Pelajar.———-. 2008. Zakat Produktif Dalam Perspektif Hukum Islam. Yogyakarta: Pustaka Pelajar. hlm. 12.Aziz, H.A, dkk. 2017. Zakat Dan Pemberdayaan. Surabaya: Airlangga University Press.Djuanda, Gustian et, al. 2006. Pelaporan Zakat Pengurang Pajak Penghasilan. Jakarta: Raja Grafindo Persada. hlm. 15-17.Hafidhuddin, Didin. 2002. Zakat Dalam Perekonomian Modern. Jakarta: Gema Insani Press.Huda, Nurul. Muhammad Heykal. 2010. Lembaga Keuangan Islam: Tinjauan Teoritis dan Praktis. Jakarta: Prenada Media Group.Mannan, Abdul. 1997. Teori dan Praktik Ekonomi Islam. Yogyakarta: PT. Dana Bhakti Prima Yasa. hlm. 285.Miftah. 2008. Pembaharuan Zakat Untuk Pengentasan Kemiskinan di Indonesia. Innovatio, Vol. VII, No. 14, Juli-Desember 2008. hlm. 425.Moleong. 1998. Metodologi Penelitian Kualitatif. Bandung: CV. Remaja Rosdakarya.———-. 2007. Metodologi Penelitian Kualitatif. Bandung: CV. Remaja Rosdakarya.Mufraini, Arief. 2006. Akutansi dan Manajemen Zakat, Mengomunikasikan Kesadaran dan Membangun Jaringan. Jakarta : Kencana Prenada Media Grup. hlm. 161.Muhammad, & Bakar, Abu. 2011. Manajemen Organisasi Zakat. Malang: Madani Wisma Kalimetro.Mu’inan, Rafi’. 2011. Potensi Zakat (dari konsumtif-karikatif ke produktif berdayaguna perspektif hukum Islam). Yogyakarta: Citra Pustaka. hlm. 132.Qardhawi, Yusuf, DR. 1999. Fiqih Az-Zakat, Bandung: Mizan.